An annotated synopsis of the powder post beetles (Coleoptera: Bostrichidae) of Mainland China - Liu, Lan-Yu (Zootaxa, 2021)
An updated and annotated synopsis of the family Bostrichidae of mainland China is presented, including sixty-eight species belonged to seven subfamilies (including eight tribes), and twenty-nine genera. Thirteen species are new records for mainland China, and numerous new provincial records are given. Four species, Dolichobostrychus yunnanus Lesne, 1913, Heterobostrychus ambigenus Lesne, 1920, Sinoxylon eucerum Lesne, 1932 and S. rejectum (Hope, 1845) are endemic to mainland China. The faunal elements present and their composition are discussed, and the zoogeographical distribution of species within mainland China.